Design Of A CAD/CAM-Simulink Data Exchange System For Machine Tool Application - Jamaludin, Zamberi; Mat Seman, Norhidayah; Minhat, Mohamad; Che Ku Junoh, Sahida (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
This paper presents design of a CAD/CAM-Simulink Data Exchange System (CS-DES) that integrates CAD/CAM software and control system architecture with the aim to further enhances capability and flexibility of a prototype milling machine. In its current state, the XY milling table positioning system is controlled using in-house designed position controller that is able to effectively control positions of the milling table using predefined reference trajectory. The application of this position controller is restricted by the signal input forms that are only available via the Simulink reference input signal library. The proposed system design allows integration of the CAD/CAM technology with the MATLAB/Simulink platform of the control system architecture, enabling variations of input signal types. The designed integrated system allows data input in the forms of Computer Aided Design and Computer Aided Machining. The main design component of the interface system was developed using MATLAB Graphical User Interactive Development Environment. This paper presents an overview of the system architecture for the CAD/CAM-Simulink data exchange system. A successful implementation of this novel data exchange system would simplify current control system development process thus providing greater flexibility and capability that could be translated into improved performance of the machine tools drives system.